Efektivitas Pendekatan Ego Untuk Meningkatkan Resiliensi Diri Siswa di SMAN 2 Padang Panjang - Wilda Hafiva; Fadhilla Yusri; Wedra Aprison (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
The purpose of this study was to determine the increase in student self-resilience through ego approach group counseling services. This type of research is quantitative experiments. The research data were obtained through a Likert scale student resilience research instrument with five alternative answers. The research design used was One Group Pretest-Postest Design. The instrument validity was tested using the Product Moment formula, and the reliability test was performed using the Alpha formula. The instrument validity test results obtained valid instrument items 52 items and 13 items are invalid with a reliability coefficient of 0.951. Based on the results of the analysis of research data after getting treatment of the ego approach group counseling services, there was an increase in self-resilience of students of class XI MIPA through ego approach group counseling services. From the results of proposing a hypothesis using the z-test formula, the value of Zhitung 2,807, while ztable is 1,833, it can be concluded that "group approach counseling services ego can increase student self-resilience". From the results of this study it is suggested that the supervising teacher should program an ego approach group counseling service so that students can increase self-resilience.